2021
DOI: 10.2217/fon-2021-0203
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Association of HER2/ ERBB2 Concordance with Trastuzumab Clinical Benefit in Advanced Esophagogastric Cancer

Abstract: Aim: To assess concordance between HER2 status measured by traditional methods and ERBB2 amplification measured by next-generation sequencing and its association with first-line trastuzumab clinical benefit in patients with advanced esophagogastric cancer. Methods: Retrospective analysis of HER2/ ERBB2 concordance using a deidentified USA-based clinicogenomic database. Clinical outcomes were assessed for patients with HER2+ advanced esophagogastric cancer who received first-line trastuzumab. Results: Overall H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…We did observe longer rwOS for patients with advGEA positive for HER2 by IHC or FISH treated with first-line trastuzumab with ERBB2 amplification detected by NGS versus those negative for amplification by NGS (Data Supplement), consistent with existing literature. 15 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We did observe longer rwOS for patients with advGEA positive for HER2 by IHC or FISH treated with first-line trastuzumab with ERBB2 amplification detected by NGS versus those negative for amplification by NGS (Data Supplement), consistent with existing literature. 15 …”
Section: Resultsmentioning
confidence: 99%
“… 15 Further exploratory analysis using median ERBB2 CN as a cutoff suggested that ERBB2 CN can be used effectively to further stratify best responders to anti-HER2 therapy, suggesting additional utility for quantitative NGS testing. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations